A Flexible Approach to the EGP Syllabus: Why It Is Possible - Mbato, Concilianus Laos (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2014)
Curriculum, and its ensuing syllabus, may reflect various competing ideologies rather than merely being a vehicle to promote quality teaching and education. In practice, English teachers may have to encounter and confront an imposed curriculum, and syllabus, in thier EGP classes. Despite such imposition, this article argues that they can and should adopt a flexible approach to the document in order to cater for learnersâ varied and changing learning needs. To achieve the aim, this article draws on theories of curriculum and discusses core issues in the teaching of English for Specific Purposes. A particular focus is then given to teaching practices in EGP classrooms where teachers interpret and implement a curriculum. A flexible model to the syllabus is offered.Â DOI: https://doi.org/10.24071/llt.2014.170104